(untitled) (UNED Research Journal, 2019)
Introduction: Charismatic species, like the panda, play an important role in conservation, and velvet worms arguably are charismatic worms. Thanks to their extraordinary hunting mechanism, they have inspired from a female metal band in Japan, to origami worms in Russia and video game monsters in the USA. Objective: To assess their conservation status in Costa Rica (according to data in the UNA Onychophora Database) and compare it with equivalent data from elsewhere. Methods: we located all collection records of the 29 species in the map of the Costa Rican Conservation Network. Results: We found that seven species are protected inside Forest Reserves, five in Protected Zones, four in Wildlife Refuges, two in National Parks and one, Principapillatus hitoyensis, in a strictly pristine Biological Reserve. The largest species in the world, Peripatus solorzanoi, occurs both inside a Forest Reserve and in protected private land. Protection inside Costa Rican nature areas is enforced year-round by personnel that includes armed guards and is supported by educational programs in surrounding communities. Twelve species have not been found in protected areas, but in Costa Rica, all biological species, named and unnamed, are protected by law and cannot be legally collected, or exported, without technically issued permits. Conclusion: Like in the only other country with similar information (New Zealand), the conservation of onychophorans seems to be of least concern for at least two thirds of the known Costa Rican species. Epiperipatus isthmicola, recently rediscovered after a century of absence in collections, can be considered Threatened because nearly all of its natural habitat has now been covered by a city.